Penggunaan Asas Derogasi dalam Penyelesaian Disharmonisasi Inventarisasi Ekspresi Budaya Tradisional - Gunawan, Kristian Vincent; Soemartono, Raden Mas Gatot Prasetyo (Kertha Patrika, 2023)
Disharmonization of regulations in the positive legal system in Indonesia often occurs in various types of regulations. One of the disharmonizations is regulations that regulate the inventory of traditional cultural expressions that aim to protect traditional cultural expressions against acts of misuse, deception, fraud, or false statements (misinterpretation), and theft or piracy (misappropriation). Inventory has a vital role as a basis for carrying out defensive protection of traditional cultural expressions. Therefore, the legal basis for an inventory of traditional cultural expressions must be clear, not disharmony. This research answers questions as to why disharmony occurs between various regulations regulating the inventory of traditional cultural expressions and how the use of the principle of derogation can resolve disharmony between regulations. Normative legal studies are the research method used in this research. The research found the disharmonization of traditional cultural expressions happened because several regulations regulate the same object, namely traditional cultural expressions, and deal with the same thing, namely inventory for defensive protection, but differently. The disharmony began from the different institutions at the central government level and the procedures for submitting data, databases, and materials. The derogation principle helps resolve the disharmony of regulations, which overrule the enforceability of regulation. In this case, the lex posterior derogate legi priori principle is used to fix the problem of disharmony in the inventory of traditional cultural expressions.